ISOLASI PROTEIN DARI AMPAS KECAP DENGAN CARA EKSTRAKSI SODA (Jurnal Teknologi Pangan, 2013)
Seed of Soy represent food-stuff having rate of protein enough is high That  is  about  35% .  Serve  the  purpose  of  raw  material  of  making  taste  in  ferment  ,  where  ketchup represent penyedap of food liked by most Indonesia society .            Protein there  are  in  ketchup only  about  7 % ,  the  rest  of  medium  follow  castaway  in  dregs  . Therefore  in this  research  require  to  be  re-taken  the  between time  of  squealer  with  protein  rate  , relation  between temperature  with  protein  rate  .  protein  which  is  there  are  in  dregs  taste  to  be  used upon which mixture in food process flesh and milk . Upon which fastener and emulsifier in product - flesh product . In this research will be learned relation between time of squealer with protein rate , relation  between temperature with protein rate.            Variable  remain  to  used  this  research  is  sieve size and  squealer  speed ,  while  for  the  variable change used by temperature at spanning : 30 – 70oC , squealer time and at spanning : 15 - 75 minute.            Intention of this research is to determine optimum time and temperature , in order to got rate of highest protein in flour of ketchup dregst           From result of this research [is] obtained [by] rate of highest protein when squealer  60 minute and temperature 60 °C, that is equal to 64,85 %.Keyword : Ketchup Dregs , Ekstraction , Protein .